2022
DOI: 10.9734/ijpss/2022/v34i2031186
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mitscherlich-bray Equation to Establish Fertilizer Recommendation for Strawberry under Adtuyon Clay Loam

Abstract: The nutrient requirement of strawberry plants is high making them very responsive to fertilization. This study utilized the Mitscherlich-Bray equation to determine the theoretical maximum yield as the basis of comparison to the actual yield. The economics of fertilizer application was also considered in the determination of the fertilizer recommendation. The theoretical maximum yield of the study is 12.29 t/ha-1. Strawberry is found responsive to nitrogen and potassium fertilization. The application of 225-225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The TEP is a linear combination of soil and fertilizer P. The nutrient efficiency coefficient, c indicates how quickly the predicted yield approaches asymptotic maximum as the TEP increases [7]. This showed that soil test should not be the only basis for fertilizer recommendation [12].…”
Section: Relationship Between Grain Yield and Tepmentioning
confidence: 99%
“…The TEP is a linear combination of soil and fertilizer P. The nutrient efficiency coefficient, c indicates how quickly the predicted yield approaches asymptotic maximum as the TEP increases [7]. This showed that soil test should not be the only basis for fertilizer recommendation [12].…”
Section: Relationship Between Grain Yield and Tepmentioning
confidence: 99%